Dignified design assessment tool - Daniel Brisson; Jennifer Wilson; Rachelle Macur; Becca Mann; Laura Rossbert; Chad Holtzinger (Frontiers in Environmental Health)
This article presents the Dignified Design Assessment Tool (DDAT), a measurement instrument that captures the concept of dignified design in the design and development of affordable housing. Dignified design is the conceptual model and within this conceptual model is the trauma informed design (TID) framework. The TID framework is now widely used in affordable housing development. This article provides an illustration and test of the content validity of the TID framework. Then, the article concludes by presenting the four item DDAT, which uses 100 word narrative responses. Instructions for administering the DDAT, and DDAT scoring guidance, are provided in the Supplementary Material.